Operational Reliability of a Periodic Railway Line - Bulíček, Josef; Drdla, Pavel; Matuška, Jaroslav (Elsevier Science BV, 2021)
The paper is focused on operational reliability of a railway line operated by periodic timetable, specifically of shuttle supplementary line creating connection to backbone line or lines. Relation between basic operational indicators (of all connected lines and interchange station) are researched by using of developed stochastic mesoscopic simulation model. Assessed relations will be helpful for evaluation of an interaction between transport operation and infrastructure within railway line capacity assessment.
Provozní spolehlivost na tratích s periodickým provozem
Keywords: railway; railway line; periodic timetable; simulation model; railway line capacity; železnice; železniční trať; periodický jízdní řád; simulační model; kapacita železniční tratě